Melanoma immunotherapy using mature DCs expressing the constitutive proteasome - Jens Dannull; N. Rebecca Haley; Gary Archer; Smita Nair; David Boczkowski; Mark Harper; Nicole De Rosa; Nancy Pickett; Paul J. Mosca; James Burchette; Maria A. Selim; Duane A. Mitchell; et al. (The Journal of Clinical Investigation, 2013)
Background. Many cancers, including melanoma, exclusively express constitutive proteasomes (cPs) and are unable to express immunoproteasomes (iPs). In contrast, mature DCs used for immunotherapy exclusively express iPs. Since proteasomes generate peptides presented by HLA class I molecules, we hypothesized that mature melanoma antigen–loaded DCs engineered to process antigens through cPs would be superior inducers of antimelanoma immunity in vivo. Methods. Subjects with metastatic melanoma were vaccinated with mature DCs transfected with RNAs encoding melanoma antigens MART1, MAGE-3, gp100, and tyrosinase. These DCs were derived from monocytes that were untransfected (Arm A; n = 4), transfected with control siRNA (Arm B; n = 3), or transfected with siRNAs targeting the 3 inducible iP subunits (Arm C; n = 5). Results. Vaccination stimulated antigen-specific T cell responses in all subjects, which peaked after 3–4 vaccinations, but remained elevated in Arm C subjects. Also in Arm C, circulating melanoma cell levels (as detected by quantitative PCR) fell, and T cell lytic activity against autologous melanoma was induced. In HLA-A2+ subjects, CD8+ T cells that bound tetramers loaded with cP-derived melanoma antigenic peptides were found in the peripheral blood only in Arm C subjects. Of 2 subjects with active disease (both in Arm C), one had a partial clinical response, while the other, who exhibited diffuse dermal and soft tissue metastases, had a complete response. Conclusion. These results suggest that the efficacy of melanoma DC–based immunotherapy is enhanced when tumor antigen–loaded DCs used for vaccination express cPs. Trial registration. Clinicaltrials.gov NCT00672542. Funding. Duke Clinical Research Institute/Duke Translational Medicine Institute, Duke Melanoma Consortium, and Duke University Department of Surgery.